SAT0117 TRIMESTER EXPOSURE AND PREGNANCY OUTCOMES IN WOMEN EXPOSED TO GOLIMUMAB – RESULTS FROM THE COMPANY PHARMACOVIGILANCE DATABASE. (13th June 2020) - Otero-Lobato, M.; Esslinger, S.; Gabriel, S.; Clark, M.; Sheridan, P.; Geldhof, A.
Abstract : Background: Rheumatologic disorders and inflammatory bowel disease can affect women of childbearing potential. Golimumab (GLM) is approved for several rheumatologic indications and ulcerative colitis (UC). Objectives: To characterize pregnancy outcomes in patients treated with GLM, data obtained from maternal exposure to GLM are presented. Methods: This dataset includes individual patient cases reported to the manufacturer through 06 April 2019. Cases included in the analysis were medically confirmed cases of maternal exposures to GLM during pregnancy or within 3 months prior to conception, and a reported pregnancy outcome. Both prospectively reported (ie, pregnancy outcome not known when first reported) and retrospectively reported cases (ie, pregnancy outcome known when first reported) were included. Cases originated from various sources, including spontaneous reporting, clinical studies, and registries. Results: Two hundred eight pregnancy cases (131 rheumatologic indications; 43 UC; and 34 other) with 211 reported birth outcomes were identified. Of these 208 pregnancy cases, 119 were prospective and 89 were retrospective. Average maternal age was 31.9 years. Of the 119 prospectively reported pregnancy cases, 89 (74.8%) resulted in live births, 19 (16.0%) resulted in spontaneous abortion (of these, 42.1% (8/19) received GLM in combination with methotrexate [MTX]), 10 (8.4%) resulted in induced/elective abortion, and 1 (0.8%) resulted in ectopic pregnancy. Overall, 9 congenital anomalies were reported (2 prospective and 7 retrospective cases). For 183 of the 208 pregnancy cases with reported outcomes, the trimester of exposure to GLM was known. Among the 110 prospectively reported cases, 82 (74.5%) were exposed during trimester 0 or 1. Of these, 19 had concomitant exposure to MTX, with the following birth outcomes: 8 live births, 8 spontaneous abortions, 3 elective/induced abortions. Eighteen of the prospectively reported cases (16.4%) were exposed to GLM through trimesters 1-3 and all resulted in live births (none with congenital anomalies; 1 infant with exposure to GLM and MTX was born preterm). Conclusion: The rates of congenital malformations and spontaneous abortions were consistent with published background rates for the general population. Persistent exposure throughout pregnancy was rare. Limitations of this analysis include the lack of a direct comparison group, the variable amount of data available in the reports, and the possible bias towards reporting more negative outcomes in retrospective cases. Disclosure of Interests: Marijo Otero-Lobato Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Suzan Esslinger Shareholder of: Johnson & Johnson, Consultant of: Johnson & Johnson, Novartis, Eli Lilly and Sandoz, Employee of: Johnson & Johnson, Susan Gabriel Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Merck, GSK, Michael Clark Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson, Pamela Sheridan Shareholder of: Johnson & Johnson, Roche Pharmaceuticals, Employee of: Johnson & Johnson, Roche, Novartis, Bayer, Anja Geldhof Shareholder of: Johnson & Johnson, Employee of: Johnson & Johnson